(Im)possibilities of an audiovisual history of Argentine Physical Education (Agora for Physical Education and Sport, 2020)
The aim is to develop a registry of unpublished audiovisual documents related to Argentine Physical Education. With the idea of establishing the possibilities of approaching its history through film material, a first access to Buenos Aires archives, exhibits a fragmentary context in diverse planes: archival dispersion, disorderly information on the origin and conservation problems. For this, a methodology is built through the archival discipline to study material from the “Centro de Documentación Histórica y Museo de la Educación Física y el Deporte”, a specialized institution with more than 200 films in different formats.
Keywords: Physical Education; Audiovisual archives; Cinematography; Bodies; Movements